1998
DOI: 10.1007/s002130050561
|View full text |Cite
|
Sign up to set email alerts
|

Effect of destruction of noradrenergic neurones with DSP4 on performance on a free-operant timing schedule

Abstract: This experiment examined the effect of destroying central noradrenergic neurones, using the selective neurotoxin DSP4 [N-(2-chloroethyl)-N-ethyl-2-bromobenzylamine], on performance in a free-operant timing schedule. Rats received either systemic treatment with DSP4 or vehicle-alone injections. They were trained to press levers for a sucrose reinforcer. Training sessions consisted of 40, 50-s trials in which reinforcers were available on a variable-interval 25-s schedule; in the first 25 s of each trial, reinfo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
5
0

Year Published

1999
1999
2012
2012

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…Response rate declined rapidly from an initially high level at the start of the trial, and a relatively constant rate of responding was maintained throughout the remainder of the trial. The initial decline of response rate has been observed previously in experiments in which VI schedules have been presented in discrete trials [28–31], and has been attributed to a reduction of arousal from a high level occasioned by the initial presentation of the operandum at the start of the trial [32].…”
Section: Discussionmentioning
confidence: 57%
“…Response rate declined rapidly from an initially high level at the start of the trial, and a relatively constant rate of responding was maintained throughout the remainder of the trial. The initial decline of response rate has been observed previously in experiments in which VI schedules have been presented in discrete trials [28–31], and has been attributed to a reduction of arousal from a high level occasioned by the initial presentation of the operandum at the start of the trial [32].…”
Section: Discussionmentioning
confidence: 57%
“…In this experiment, as in some previous experiments (Fetterman and Killeen 1995;Al-Zahrani et al 1996, there was a progressive decline in overall response rate during the course of the trial. Killeen et al (1997) have suggested that this intra-trial decline in response rate may reflect a progressive reduction of arousal from a high level occasioned by the initial presentation of the operanda at the start of the trial (see also Al-Zahrani et al 1998).…”
Section: Discussionmentioning
confidence: 96%
“…Indeed, in our experiments, MAP shifted the peak time in opposite directions in probe trials with or without gaps—indicative of both clock and attentional effects—whereas HAL shifted the peak time significantly in trials with gaps, but only marginally in trials without gaps—indicative of predominantly an attentional effect rather than a clock-speed effect. On the other hand, results might have been due to the activation of the noradrenergic (Al-Zahrani, Al-Ruwaitea, Ho, Bradshaw, & Szabadi, 1998) or serotonergic systems (Chiang, Al-Ruwaitea, Ho, Bradshaw, & Szabadi, 1999). Additional pharmacological, neurophysiological and genetic manipulations using the behavioral paradigms described here will help elucidate the biological substrates of the attentional mechanisms of interval timing.…”
Section: Discussionmentioning
confidence: 99%